Patterns of brain structure-function coupling variations related to height and growth hormone in children with short stature - Lu, Yi; Chen, Xiaojun; Tang, Jing; Yang, Yang; Yang, Tao; Shan, Xiaoou; Yan, Zhihan; Liu, Xiaozheng (Pediatric research, 2025)
Adolescents with varied growth hormone (GH) levels exhibit height discrepancies. This study investigated the association of height and GH on structural-functional connectivity (SC-FC) coupling within brains of growth hormone deficiency (GHD), idiopathic short stature (ISS), and healthy controls (HC). Retrospective analysis of 79 GHD, 88 ISS, and 37 HC subjects was performed, incorporating clinical, behavioral assessments, and multimodal brain MRI data. SC-FC coupling matrices were derived from diffusion tensor imaging (DTI) and resting-state functional MRI (rs-fMRI). Group comparisons used ANOVA and Tukey HSD tests, while partial correlation assessed correlations of hormone levels and cognitive scores. Both short-statured groups (GHD and ISS) displayed reduced hormone levels, cognitive behavioral scores, and SC-FC coupling in primary sensory regions (visual (VIS) and sensorimotor network (SMN)) compared to HC. Bilateral SMN showed the highest intra-network variability amongst all groups. GHD exhibited greater inter-network SC-FC coupling variability than ISS, with HC showing the least. A negative correlation between peak GH levels and SC-FC coupling across multiple networks was observed exclusively in GHD. Height and GH distinctly influenced brain structure-function coupling in children with short stature. Reduced SC-FC coupling in primary sensory regions highlights their vulnerability to developmental variations. The study demonstrates that height and growth hormone (GH) levels have distinct impacts on brain structure-function coupling (SC-FC) in children with short stature, with primary sensory regions (e.g., visual and sensorimotor networks) being particularly vulnerable. The findings highlight the susceptibility of primary sensory brain regions to developmental variations and suggest that GH plays a critical role in modulating brain connectivity, particularly in the GHD group. The study underscores the importance of early intervention for children with GHD, as reduced SC-FC coupling in primary sensory regions may correlate with cognitive and behavioral outcomes.